Social Cognition in Schizophrenia and Autism Spectrum Disorders: A Systematic Review and Meta-Analysis of Direct Comparisons - Fernandes, João Miguel; Cajão, Rute; Lopes, Ricardo; Jerónimo, Rita; Barahona-Corrêa, J. Bernardo (Frontiers in Psychiatry, 2018)
Background: Deficits in social cognition are well-recognized in both schizophrenia and autism spectrum disorders (ASD). However, it is less clear how social cognition deficits differ between both disorders and what distinct mechanisms may underlie such differences. We aimed at reviewing available evidence from studies directly comparing social cognitive performance between individuals with schizophrenia and ASD. Methods: We performed a systematic review of literature up to May 22, 2018 on Pubmed, Web of Science, and Scopus. Search terms included combinations of the keywords “social cognition”, “theory of mind”, “autism”, “Asperger”, “psychosis”, and “schizophrenia”. Two researchers independently selected and extracted data according to PRISMA guidelines. Random-effects meta-analyses were conducted for performance on social cognitive tasks evaluating: 1) emotion perception; 2) theory of mind (ToM); 3) emotional intelligence (managing emotions score of the Mayer-Salovey-Caruso Emotional Intelligence Test); and 4) social skills. Results: We identified 19 eligible studies for meta-analysis including a total of 1,040 patients (558 with schizophrenia and 482 with ASD). Eight studies provided data on facial emotion perception that evidenced a better performance by participants with schizophrenia compared to those with ASD (Hedges’ g=0.43; p=0.031). No significant differences were found between groups in the Reading the Mind in the Eyes Test (8 studies; Hedges’ g=0.22; p=0.351), other ToM tasks (9 studies; Hedges’ g=-0.03; p=0.903), emotional intelligence (3 studies; Hedges’ g=-0.17; p=0.490), and social skills (3 studies; Hedges’ g=0.86; p=0.056). Participants’ age was a significant moderator of effect size in emotion perception and RMET analyzes, with larger differences favoring patients with schizophrenia being observed in studies with younger participants. Conclusions: The instruments that are currently available to evaluate social cognition poorly differentiate between individuals with schizophrenia and ASD. Combining behavioral tasks with neurophysiologic assessments may better characterize the differences in social cognition between both disorders.